Deep Cervical Lymphovenous Anastomoses Improved Brain Function and Internal Neck Edema in Central Lymphatic Anomaly Associated with 13q Deletion Syndrome - Donata von Reibnitz, MD; Jacqueline Plau, PhD; Gilbert D. Puippe, MD; Claus C. Pieper, MD; Epameinondas Gousopoulos, MD, PhD; Nicole Lindenblatt, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. We report a case of a 21-year-old woman with 13q deletion syndrome, a rare chromosomal disorder associated with developmental delays, craniofacial dysmorphism, and multiorgan abnormalities associated with central conducting lymphatic anomaly. Her symptoms included bilateral chylothorax, pulmonary lymphangiectasis, generalized edema, and recurrent respiratory distress. Despite conservative management, her condition progressively worsened, leading to significant edema affecting the tongue and upper airway. Magnetic resonance lymphangiography revealed a severe central lymphatic flow disorder with reflux into the pulmonary and cervical regions. Given the lack of further medical options, a thoracic duct-vein anastomosis in the left neck was planned in May 2023 to improve drainage. However, no distinct thoracic duct was identifiable during the procedure. Therefore, multiple deep cervical lymphovenous anastomoses (LVAs) were performed. Postoperatively, the patient experienced significant improvements in respiratory function, resolution of tongue and airway edema, and cessation of diuretic therapy. Her neurological and cognitive functions improved, with better communication, increased attention span, reduced ataxia, and improved motor control. This underscores a possible link between enhanced lymphatic drainage and brain function. Follow-up imaging showed reduced lymphatic reflux in the central system. This is the first reported case of central conducting lymphatic anomaly in a 13q deletion syndrome patient, highlighting the complexities of lymphatic reconstructive surgery in such cases. Deep cervical lymphovenous anastomoses may not only alleviate lymphatic dysfunction but also improve cognitive function by enhancing glymphatic drainage, supporting emerging evidence that lymphatic surgery may improve neurological dysfunction. Further research is needed to explore this potential therapeutic avenue.